2012
DOI: 10.1634/theoncologist.2011-0276
|View full text |Cite
|
Sign up to set email alerts
|

Results of the GYNECO 02 Study, an FNCLCC Phase III Trial Comparing Hysterectomy with No Hysterectomy in Patients with a (Clinical and Radiological) Complete Response After Chemoradiation Therapy for Stage IB2 or II Cervical Cancer

Abstract: Learning Objectives After completing this course, the reader will be able to: Evaluate the therapeutic impact of hysterectomy after chemoradiation therapy in locally advanced cervical cancer. Evaluate the rate of histologic residual disease in patients with complete clinical and radiologic response after chemoradiation therapy. This article is available for continuing medical education credit at http://CME.TheOncologist.com Background. Concomitant chemoradiation (CRT) (including brachytherapy) is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 27 publications
2
72
0
5
Order By: Relevance
“…Recently, Duenas-Gonzalez et al reported the results of a phase III trial that showed that gemcitabine plus cisplatin chemoradiotherapy followed by adjuvant gemcitabine/cisplatin chemotherapy improved survival outcomes [24]. Hysterectomy may also be considered as an adjunctive treatment option for high-risk patients after CCRT, although this possibility is only supported by limited evidence [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Duenas-Gonzalez et al reported the results of a phase III trial that showed that gemcitabine plus cisplatin chemoradiotherapy followed by adjuvant gemcitabine/cisplatin chemotherapy improved survival outcomes [24]. Hysterectomy may also be considered as an adjunctive treatment option for high-risk patients after CCRT, although this possibility is only supported by limited evidence [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…After completion of a randomized study, evaluating the role of systematic hysterectomy in patients with complete clinical and radiologic remission (GYNECO 02), this strategy was abandoned [7], and hysterectomy was considered as a salvage treatment, and therefore limited to patients with histologically proven incomplete local response. The inclusion period started from the abandon of post radiation hysterectomy until 2011.…”
Section: Treatmentmentioning
confidence: 99%
“…proctitis, cystitis, hydronephrosis) resulted lower compared to exclusive CTRT probably because of replacement of utero-vaginal brachytherapy with completion surgery [4]. Among major criticisms raised against CTRT followed by radical surgery are the potential higher risk of long-term complications together with the potential depletion of all available treatment modalities for the recurrent disease [4][5][6]. Indeed, the treatment choice for recurrent disease is primarily dependent on previous therapy and secondarily on the site of the recurrent tumor together with the patient's performance status [7,8].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%